Online Scientific Writing Training for Students of Unika Santu Paulus Ruteng and Semarang State University (International Journal of Active Learning, 2022)
The condition of the Covid-19 pandemic which requires staying at home has made many changes, especially in the field of education. Semarang State University (UNNES) and Unika Santu Paulus Ruteng are universities affected by the Covid-19 pandemic so that online learning has an effect on the graduation of old students.  Thesis and scientific publications are quite a big obstacle for students who are currently thesising.  Scientific articles including the publication of scientific papers are one of the causes of this because it is still a scary thing for students. UNNES and Unika Santu Santu Paulus Ruteng students who are carrying out S1 research (thesis / final project) are very much scattered throughout the study program. This service is carried out to overcome these problems, both in Unika and UNNES. The Technical Guidance Method is used in this service in overcoming these problems which are carried out online because the spread of the Omicron variant of Covid-19 and the distance between the two universities is very far. This devotion produces the output of articles created by trainees. In the article, it is found that a) the scientific article in the aspects of completeness is in the good group, b) the content of the draft article is in the excellent, good, and quite good group. However, in terms of EYD, there were 18 errors in the use of the conjunction "sedangkan" there were 18 errors from 26 participants, inaccuracy in terms of the use of the affirmative conjunction "yaitu” as many as 91 errors, and inaccuracy in the use of comma punctuation (,) before the word "yaitu" as many as 126 errors.Keywords: training, scientific articles, UNNES and Unika Santu Paulus Ruteng students